Gerenciamento de resíduos de laboratórios de ensino e pesquisa: estudo de caso da Universidade Tecnológica Federal do Paraná - Campus Toledo - Frigori, Ana Cecília Bonfleur (2021)
There has been an increasing global concern about the environmental issue, but there has been an absence of a solid waste management plan that involves the entire society in various segments. In this work we analyze the existence of a specific Waste Management Plan for the Teaching and Research Laboratories of the Federal Technological University of Paraná – Campus Toledo. And also analyze the application of the Law nº. 12,305/10, which institutes the National Solid Waste Policy, taking into account the great difficulty that universities have to manage the disposal of these wastes, since these are specific and not constant, varying according to the research. The methodology used in this research was a case study with the analysis of five teaching and research laboratories, and bibliographic, documentary and descriptive research was also used. We carried out questionnaires to the servers, professors and students who use most these laboratories, to seek information on the best way to manage this wastes, which, even though a small amount, can be harmful to the environment if not disposed of incorrectly, respecting a management plan.